Switching and finite automata theory - Kohavi, Zvi (Tata McGraw-Hill, 2008)
Switching and finite automata theory / Kohavi, Zvi. -- New Delhi: Tata McGraw-Hill, 2008 006.3 K79e2 2nd ed. No. of Copies : 1